2015
DOI: 10.15672/hjms.201510314219
|View full text |Cite
|
Sign up to set email alerts
|

Linear Penalized Spline Model Estimation Using Ranked Set Sampling Technique

Abstract: Benefits of using Ranked Set Sampling (RSS) rather than Simple Random Sampling (SRS) are indeed significant when estimating population mean or estimating linear models. Significance of this sampling method clearly appears since it can increase efficiency of the estimated parameters and decrease sampling costs. This paper investigates and introduces RSS method to fit spline and penalized spline models parametrically. It shows that the estimated parameters using RSS are more efficient than the estimated paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The efficiencies of regression analysis with RSS data in Muttlak (1995) are slightly more than the corresponding ones with SRS data. Similar performances were observed in Al Kadiri (2016), Algarni (2016), andAl Kadiri (2017), where they also used the OLS approach to estimate the nonlinear relationships between X[š‘Ÿ]š‘— and š‘¦ [š‘Ÿ]š‘— using spline regression models. In all these studies, RSS-based models have shown slight improvements in the relative efficiencies.…”
Section: Current Methods For Regression Analysis With Rss Datamentioning
confidence: 55%
See 4 more Smart Citations
“…The efficiencies of regression analysis with RSS data in Muttlak (1995) are slightly more than the corresponding ones with SRS data. Similar performances were observed in Al Kadiri (2016), Algarni (2016), andAl Kadiri (2017), where they also used the OLS approach to estimate the nonlinear relationships between X[š‘Ÿ]š‘— and š‘¦ [š‘Ÿ]š‘— using spline regression models. In all these studies, RSS-based models have shown slight improvements in the relative efficiencies.…”
Section: Current Methods For Regression Analysis With Rss Datamentioning
confidence: 55%
“…In this paper, we proposed two approaches for regression analysis in the prediction problems context using RSS data. We show that our proposed methods provide efficient approaches to imbed the extra rank information of RSS data into the construction of more efficient predictive models and our fitted models are more efficient than the current ones based on the OLS methodology (Muttlak, 1995;Algarni, 2016;Al Kadiri, 2017). We showed that under the RSS design, the error terms associated with order statistics in their corresponding regression models have different distributions with different variances and one can use a weighted least squares method or a multilevel modeling approach to incorporate the rank information of such data and develop better predictive models than those with SRS data.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations